Floristic Composition, Diversity, and Vegetation Structure of Woody Species in Kahitassa Forest, Northwestern Ethiopia - Baymot Workayehu; Daniel Fitamo; Firew Kebede; Liyew Birhanu; Amare Fassil (International Journal of Forestry Research)
Kahitassa forest is one of the State Forests of Ethiopia with great floral diversity. However, the forest is under threat due to selective cutting of important indigenous tree species and encroachment of the forest area for agricultural purpose. Therefore, the study was intended to explore the floristic composition, structure, and regeneration status of Kahitassa forest. Vegetation data were collected from June to November 2020 using systematic sampling technique from 6 parallel transect lines laid out 500 m apart each other. A total of 101 plots (20 × 20 m) were laid with 100 m apart along transect lines. Vegetation description parameters including Shannon–Weiner Index, evenness, density, DBH, basal area, frequency, and importance value indices (IVI) were computed to characterize both species diversity and vegetation structure. Hierarchical cluster analysis was used to identify plant communities using R (Version 3.1.2) software. A total of 46 woody plant species belonging to 45 genera and 36 families were identified in the forest. Fabaceae and Rosaceae were the dominant families both constituting 34.78% of the total species. The Shannon diversity index (H’) and evenness (E) values of the study area were 2.92 and 0.72, respectively, showing the healthy status of the forest. Five plant community types, namely, Croton macrostachyus–Embelia schemperi, Maytenus undata–Olea europaea subsp. cuspidata, Pavetta abyssinica–Bersama abyssinica, Peucadanum mattiroli, Albizia schimperiana, and Rubus apetalus–Phytolacca dodecandra were identified. The most dominant species as indicated by their important value index (lVI) were Pavetta abyssinica (34.08), Vachellia abyssinica (IVI = 25.13), and Albizia schimperiana (IVI = 21.45). Analyses of DBH revealed that the forest exhibits an inverted J-shape which is typical for selective cutting of multipurpose trees from the forest. Conservation approaches such as enrichment of selected species as well as in situ and ex situ conservation are needed for some plant species under threat.